2019
DOI: 10.3389/fnut.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Polyphenol Content to Uncork the Relationship Between Wine and Cancer

Abstract: Studies have revealed conflicting results regarding the risk of cancer from alcohol consumption. Furthermore, some studies have suggested that wine may have benefits that separate it from other alcoholic beverages. As wine contains a significant amount of chemicals, specifically polyphenols like anthocyanins and proanthocyanidins (PA), that can affect cellular function and promote health, this hypothesis is reasonably supported by recent research. Polyphenols promote several anticancer cellular pathways, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 177 publications
0
14
0
Order By: Relevance
“…They are responsible for some of the characteristics and sensory features of wine. Regarding phenolic constituents, or polyphenols, also present in fruit, grains, and vegetables, data from several studies suggest that they have healthy properties [ 1 , 6 , 7 , 8 ]. Resveratrol, a non-flavonoid present in trace quantities, is a natural antioxidant and anti-inflammatory compound, known to play a key role in immunoregulation, metabolic syndrome, cardiovascular, neuroprotection, and cancer treatment [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introduction: An Overview Of Wine To the Past From The Prmentioning
confidence: 99%
“…They are responsible for some of the characteristics and sensory features of wine. Regarding phenolic constituents, or polyphenols, also present in fruit, grains, and vegetables, data from several studies suggest that they have healthy properties [ 1 , 6 , 7 , 8 ]. Resveratrol, a non-flavonoid present in trace quantities, is a natural antioxidant and anti-inflammatory compound, known to play a key role in immunoregulation, metabolic syndrome, cardiovascular, neuroprotection, and cancer treatment [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introduction: An Overview Of Wine To the Past From The Prmentioning
confidence: 99%
“…The ROS level in the A549 cell line was investigated to assess whether ROS played a significant role in the induction of apoptosis after exposure to punicalagin. According to several studies in which ROS levels in tumour cell lines after exposing them to polyphenol or flavonoids were measured, the induction or reduction of ROS levels lead to cell death (Renis et al 2008;Singh et al 2011;Yahfoufi et al 2018;Yang et al 2018;Champ and Kundu-Champ 2019). Li et al (2016) demonstrated that pomegranate leaf extract induced ROS level and loss of mitochondrial transmembrane potential in lung cancer cells.…”
mentioning
confidence: 99%
“…Earlier comprehensive reviews on the classification, synthesis, and properties of phenolics have been reported [30,31]. Briefly, phenolics are classified into groups that include phenolic acids, flavonoids, tannins, stilbenes, lignins, and coumarins [31] and as secondary plant metabolites, they provide a self-defence role for the plants as they help the plants ward off foreign invaders [32]. Harsh environmental factors have been found to impact on the development of bioactive compounds in plants [32].…”
Section: Bioactive Properties Of Plant-based Food By-products From Inmentioning
confidence: 99%
“…Briefly, phenolics are classified into groups that include phenolic acids, flavonoids, tannins, stilbenes, lignins, and coumarins [31] and as secondary plant metabolites, they provide a self-defence role for the plants as they help the plants ward off foreign invaders [32]. Harsh environmental factors have been found to impact on the development of bioactive compounds in plants [32]. For example, plants that grow at high mountainous areas, drought areas, and in high salinity conditions naturally develop a high concentration of bioactive compounds compared to their counterparts that grow under normal conditions [32].…”
Section: Bioactive Properties Of Plant-based Food By-products From Inmentioning
confidence: 99%
See 1 more Smart Citation